GE_GERICHTE P/16133/2020 vom 16. Juli 2021 - GE Cour de justice (2021)
FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;EXPULSION(DROIT DES ÉTRANGERS) | CP.140.ch1; CP.139.ch1; LEI.115.al1.leta; LEI.115.al1.letb; LStup.19a.ch1; CP.66a.al1; CP.47; CP.49.al1